Petrology and geochemistry of late intermediate period ceramics, Southern Peru - Oestreich, Daniela B.; Glasmacher, Ulrich A.; Reindel, Markus (Archaeometry, 2017)
Multiple petrological and geochemical analytical techniques revealed significant similarities in element and mineral distribution between the 47 ceramic samples from Chillo (southern coast, Peru), a Late Intermediate Period (ad 1000-1400) archaeological site. The similarity indicates a common raw material source. The analytical results of Holocene fluvial sediment samples, Cretaceous clay layers and fired and non-fired bricks, only eliminated the Cretaceous clay layers as a potential source material. Applying Raman spectroscopy, the red and violet colour of the slip is due to hematite, the yellow colour to a mixture of hematite, graphite and gypsum, and the black colour is either graphite or jacobsite.
Gesehen am 11.07.2017